Effects of Deep Breathing Exercise and Exercise Therapy on Pain in Postoperative Scoliosis Patients - Renni Hidayati Zein; Ismaningsih; Nanda Shifatussholiha; Atika Afniratri (POLTEKKES KEMENKES PONTIANAK, 2025)
Scoliosis is a spinal disorder that causes an abnormal sideways curvature of more than 10 degrees and can have a significant impact on quality of life. In severe cases of scoliosis, surgery is performed to prevent the progression of the curvature. However, postoperative pain (post op scoliosis) is one of the main complaints that can hinder the recovery process. This study aims to evaluate the effectiveness of Deep Breathing Exercise and Exercise Therapy interventions in reducing pain in post op scoliosis patients. The case study was conducted on one patient who underwent intervention six times from 20 April to 2 May 2025. Pain evaluation was performed using Visual Analogue Scale (VAS) every therapy session. The results showed a decrease in pressure pain from a score of 4 to 2 and motion pain from a score of 6 to 4, with silent pain remaining at a score of 0. This decrease indicates that the combination of Deep Breathing Exercise and Exercise Therapy interventions is effective in reducing pain in postoperative scoliosis patients.